Keanekaragaman dan kelimpahan arhtropoda tanah pada lahan cabai dengan perlakuan bioremediasi - Ratna Rubiana; Araz Meilin (Jurnal Entomologi Indonesia, 2022)
The level of contaminants in the land can be reduced by remediation. Remediation allows to destroy or makes contaminants into harmless using natural biological activities (bioremediation). Land conditions before and after bioremediation treatment is uses some kind of arthropods land as an indicator of soil fertility. This study aims to assess the factors affect diversity, compare the structural similarity, and species composition of soil arthropods as bioindicators of the recovery of soil biological properties in chili cultivation. Soil arthropod sampling was carried out on chili farmers’ fields with 5 bioremediation treatments in Sangir Tengah Village, Kayu Aro District, Kerinci Regency, Jambi Province with the pitfall trap method that was installed for 2 nights. The bioremediation treatments were control (without bioremediation), and 4 bioremediation treatments (trichocompos 10 tons/ha, trichocompos + bagasse biochar at a dose of 2 tons/ha, trichocompos + corncob biochar at a dose of 2 tons/ha, and trichocompos + rice husk biochar at  a dose of 2 tons/ha. The results showed that there were 9,712 individuals belonging to 10 orders and 28 species of soil arthropods. The diversity of soil arthropods in the bioremediation treatment showed significant differences (R = 0.3953; P < 0.001). The Shannon-Wiener diversity index was highest in the control land as well as the evenness index (E) which means that the bioremediation treatment had no effect on the diversity of soil arthropods. Bioremediation treatment on chili fields did not show an increase in the number of orders and species.